The nth term is 5n-3 and so the next term will be 22
5n - 3
The nth term is given by: rn = n2 + 8
If you meant: 2 12 22 32 then the nth term = 10n-8
It is: nth term = 7n-9
nth term= 6 + (n-1) (2)
The nth term is 3n+2 and so the next number will be 17
The nth term is (2n - 12).
The sequence is simply achieved by adding 2 to each value9+2=1111+2=1313+2=1515+2=1717+2=1919+2=21so the nth term can be calculatedThe value of the nth term = the value of (nth-1 term) +2.
It is: 3n+2
The nth term is: 3n+2 and so the next number will be 20
12 - 5(n-1)
The nth term would be -2n+14 nth terms: 1 2 3 4 Sequence:12 10 8 6 This sequence has a difference of -2 Therefore it would become -2n. Replace n with 1 and you would get -2. To get to the first term you have to add 14. Therefore the sequence becomes -2n+14. To check your answer replace n with 2, 3 or 4. You will still obtain the number in the sequence that corresponds to the nth term. :)
It is: nth term = -4n+14
The sequence goes up by 5 each time; the first term is two. So the nth term is 2 + 5n. n=50 => 2+50*5 = 252.
3n - 1
The sequence has a difference of 10, so the nth term starts with 10n. Then to get to -8 from 10 you need to subtract 18. So the nth term is 10n - 18.
5 to 7 is 27 to 17 is 1017 to 19 is 219 to 29 is 1029 to 31 is 2there fore following the pattern the nth term is 4131 to 41 is 10
The nth term is 2n
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .